Nesporazumi z medijem - Hladnik, Miran (Primerjalna književnost, 2017)
Current alternative messaging possibilities, in particular the internet, urge consideration of mediality and (or conveyance of) literature - that is, of how media shape and determine a message. Errors and misunderstandings that arise as media change and users remain inert point up the specificities of media (both print and screen). There is evidence of misunderstandings in literary and related scholarly communications caused by a text's format, page length, concept of authorship, manipulability, openness, genre hybridity and officiality, open access culture, altered understanding of what it means to be published, new possibilities for archiving, and means of referencing and citing. The experiential sources were a Wikisource project aimed at copying the entire Slovenian literary production in the public domain onto the internet, scholarly communications in the SlovLit discussion list, and preparing an on-line textbook, Nova pisarija, for publication in print.
Keywords: authorship; avtorstvo; citation; citiranje; electronic media; elektronski mediji; free access; literatura in mediji; literature and media; objavljenost; print; printing; prosti pristop; publishing; spletna besedila; tisk; web texts